Does intergenerational social mobility affect the general health, oral health, and physical function of older adults in England?. (November 2016) - Letelier, Alejandra; Heilmann, Anja; Watt, Richard G; Jivraj, Stephen; Tsakos, George
Abstract: Background: Socioeconomic status (SES) affects adult health. Material disadvantage experienced in childhood or adulthood is related to high adult disease levels. However, people transition through different socioeconomic paths over the life course. Changes in SES might counteract the effect of childhood SES on adult health, and research on social mobility takes this possibility into account by adopting a trajectory approach and taking a long-term view of the effect of SES on health. The aim of this research was to examine the effects of intergenerational social mobility on adult general health, oral health, and physical functioning in older adults in England. Methods: This study is based on secondary analysis of data from the English Longitudinal Study of Ageing, which follows the lives of about 12 000 English adults aged 50 and over. Data from waves three and four of the study, were used to create nine social trajectories based on parental and adult occupational SES, resulting in three upwardly mobile, three downwardly mobile, and three stable groups. Regression models were used to estimate the associations between social trajectories and the following outcomes: self-rated health, self-rated oral health, oral-health-related quality of life, total tooth loss, and grip strength, while controlling for socioeconomic background and health-related behaviours. Findings: Intergenerational social mobility was associated with self-rated health (p<0·05 for six of nine trajectories), total tooth loss (p<0·05 for six of nine trajectories), and grip strength (p<0·05 for five of nine trajectories) in the expected direction. For individuals moving one step between middle and low SES, moving upwardly resulted in better health and function than for individuals moving downwardly; the same finding was observed for individuals moving two steps between high and low SES. However, no associations were observed for oral-health-related quality of life and self-rated oral health. Compared with the stable high SES group, remaining in low SES over time was associated with poorer health for all outcomes (odds ratios for general health 4·27, 95% CI 3·47 to 5·27; oral health 1·52, 1·20 to 1·92; tooth loss 6·78, 5·04 to 9·12; oral-health-related quality of life 1·64, 1·11 to 2·43; and β coefficient for grip strength −4·35, −5·60 to −3·11). Adjustment for adult education partly explained these associations. Interpretation: The results suggest that social mobility is an important determinant of health and function; downward mobility led to worse health and upward mobility led to better adult health. However, for oral health, social mobility is related to lifetime accumulation of oral diseases (total tooth loss) rather than current perception of oral health and quality of life. Funding: None.